Changing the Meaning of Night: Educational Tourism in Mycelia Forest Cikole - Astia, Ella Dewi; Gitasiswhara, Gitasiswhara (Indonesian Journal of Tourism and Leisure, 2026)
This study focuses on the application of educational tourism in night adventure activities in the Mycelia Forest, Cikole, by reviewing marketing communication strategies, tourist experiences, mindset transformation, and the impact on local communities. The research method used was qualitative through semi-structured interviews with 20 informants and field observations. The results of the study show that: (1) education is delivered through the creative integration of video mapping, animation, storytelling guides, information boards, and interactive rides; (2) tourists experience enjoyable organic learning without feeling like they are in a formal setting; (3) there is a transformation in tourists' mindset about educational tourism from formal and boring to creative and enjoyable; (4) the uniqueness of night adventures creates strong differentiation that drives loyalty and word-of-mouth; (5) destinations have a positive impact on local communities through economic improvement, area image, and infrastructure. This research contributes to the development of sustainable, transformative educational tourism strategies that have a positive impact on both tourists and local communities.